The Role of Revenue Volatility in Local Expenditure Volatility: A Comparison of Tokyo Metropolitan Local Governments. Issue 4 (12th September 2018) - Tran, Thien Vu; Drew, Joseph; Noguchi, Masayoshi
Abstract : Local expenditure volatility can have significant implications for the health of local economies. It is therefore essential to understand how fluctuations in the various components of municipal revenue translate into expenditure volatility. We examine the association between revenue and expenditure volatility for Tokyo Metropolitan Governments – which are comprised of both Special Wards and Tama Cities – through recourse to a six‐year panel of fiscal data (2010–2015 inclusive). We find evidence of statistically significant positive associations between the volatility of most local taxes and expenditure volatility, but negative associations between the volatility of grants and expenditure volatility. This suggests that grants play an important role in smoothing out local expenditures in Tokyo and that the prescription for greater reliance on local taxation, found in much of the literature, may not be appropriate for Japanese local governments.